Open source IOT monitoring and controlling system using raspberry Pi 3 and OpenHAB to measure and control the electricity power consuming - Ali Al-Abri, Ghalib; Abbas, Mohamed; Balusamy, Balamurugan; Kadry, Seifedine (International Journal of Engineering and Technology, 2019)
Internet of Things (IoT) is one of promised components of Industry 4.0. It is a concept of how to the technology make the life easy and smart enough to let people focus on more productive and efficient areas. The ultimate purpose of this research paper is to introduce a practical experience of adopting open source solutions which a world trend to solve daily issues quickly, efficiently and affordably. Open source initiatives believe that community is a key party to contribute with solutionsâ€™ ideas, technical experience and sharing knowledge.Â Â